Solar energy potential assessment in the Slovenska Bistrica municipality - Arzenšek, Špela; Davidovič, Danijel; Ivajnšič, Danijel (Journal for Geography, 2020)
The research demonstrates the methodological implementation of lidar data for assessment of solar energy potential for electricity generation in the case of municipality Slovenska Bistrica. First, Uniform Sky and Standard Sky models were used to calculate quantity and duration of global solar radiation on potential areas on building roofs, which were identified with an accurate digital surface model and building cadastre. The digital surface model was also used to determine the characteristics of roofs that influence the utilisation of solar potential, such as total availible area, slope and aspect. Further, the solar potential of the entire municipality was estimated based on the actual data of three selected solar power plants. Finally, the ANOVA test was performed to verify the differences between actual and calculated values. This approach is useful for planning the energy self-sufficiency of individual households, local communities, businesses and municipalities, which can strengthen energy security and thus reduce the impact of climate change.